1975
DOI: 10.1128/aac.7.5.640
|View full text |Cite
|
Sign up to set email alerts
|

Empiric Therapy for Cancer Patients: Comparative Study of Ticarcillin-Tobramycin, Ticarcillin-Cephalothin, and Cephalothin-Tobramycin

Abstract: Three combinations of antibiotics (cephalothin-tobramycin, cephalothinticarcillin, and ticarcillin-tobramycin) were administered empirically to 186 patients with cancer who were suspected of having a life-threatening infection. In approximately one-half of these patients, gram-negative infection was documented bacteriologically and consisted of septicemia in 50% of these patients. The three antimicrobial regimens were similarly effective and resulted in a favorable clinical response in approximately 55% of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0
3

Year Published

1977
1977
1988
1988

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(29 citation statements)
references
References 15 publications
2
24
0
3
Order By: Relevance
“…In clinical studies, Klastersky et al (8) have reported better responses in cancer patients treated with combinations of antibiotics, including ticarcillin + tobramycin, that were synergistic than with nonsynergistic combinations. More recently, Parry and Neu (16) found that ticarcillin + tobramycin compared favorably with ticarcillin alone, or with ticarcillin + gentamicin, in eradicating P. aeruginosa from the sputum of patients with cystic fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical studies, Klastersky et al (8) have reported better responses in cancer patients treated with combinations of antibiotics, including ticarcillin + tobramycin, that were synergistic than with nonsynergistic combinations. More recently, Parry and Neu (16) found that ticarcillin + tobramycin compared favorably with ticarcillin alone, or with ticarcillin + gentamicin, in eradicating P. aeruginosa from the sputum of patients with cystic fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…In 262 patients given an aminoglycoside plus ticarcillin, definite nephrotoxicity occurred in 8 patients (3.1%); in 126 patients given an aminoglycoside plus cephalothin, definite nephrotoxicity occurred in 23 patients (18.3%). Two prospective studies in neutropenic cancer patients found definite nephrotoxicity in 2 and 6% of the febrile neutropenic patients given either carbenicillin or ticarcillin with an aminoglycoside (10,11). A protective effect of the penicillin therapy can only be inferred, as treatment protocols did not include a group of patients that received an aminoglycoside only.…”
Section: Discussionmentioning
confidence: 99%
“…This concept is consistent with a previous report which showed that the simultaneous administration of carbenicillin in rats reduced the nephrotoxicity of gentamicin (4). Furthermore, febrile neutropenic cancer patients have exhibited a low frequency of nephrotoxicity after treatment with an aminoglycoside plus an antipseudomonal penicillin (10,11,22). The relative paucity of studies and the potential clinical benefit of reduced aminoglycoside nephrotoxicity prompted the current experiments.…”
mentioning
confidence: 99%
“…Various antimicrobial regimens have been used, including the combination of an anti-pseudomonal penicillin, ami noglycoside and cephalosporin [Bloom field and Kennedy. 1974;Klastersky et al, 1971Klastersky et al, , 1974Klastersky et al, , 1975Middleman el al., 1972;Schimpffet al, 1971;EROTC Internation al Antimicrobial Therapy Project Group, 1978]. In spite of such advances in anti microbial therapy, infection remains one of the major problems.…”
Section: Introductionmentioning
confidence: 99%